2003
DOI: 10.1176/appi.ajp.160.5.1002
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder in Adolescent Schizophrenia Patients

Abstract: A substantial proportion of adolescent schizophrenia inpatients have concomitant OCD. A prospective study is needed to evaluate the clinical course, response to treatment, and prognosis for this complex disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
3
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 15 publications
6
48
3
7
Order By: Relevance
“…This finding contradicts other studies that report a worse outcome and higher levels of positive and negative symptoms in patients with comorbid schizophrenia and OCD (5)(6)(7)(8). Recently, it was found that adolescent schizophrenia patients with OCD had higher affective flattening or blunting scores than those without OCD (9). Most of these studies are limited by cross-sectional design, inclusion of patients in different stages of their illness, and the inability to control for confounders such as the effects of chronicity or long-standing treatment effects.…”
contrasting
confidence: 56%
“…This finding contradicts other studies that report a worse outcome and higher levels of positive and negative symptoms in patients with comorbid schizophrenia and OCD (5)(6)(7)(8). Recently, it was found that adolescent schizophrenia patients with OCD had higher affective flattening or blunting scores than those without OCD (9). Most of these studies are limited by cross-sectional design, inclusion of patients in different stages of their illness, and the inability to control for confounders such as the effects of chronicity or long-standing treatment effects.…”
contrasting
confidence: 56%
“…Four patients exhibited obsessive compulsive symptoms, which has been reported in both TS and in schizophrenia [39,40]. The presence of learning disabilities in individuals with TS and/or ADHD is also not surprising, nor is it so with schizophrenia, especially in light of recent research into the neurocognitive impairments present in that disorder [41,42].…”
Section: Discussionmentioning
confidence: 89%
“…Our finding showed that 39.3% of the subjects with OCD, 6.5% of the subjects with subthreshold OCD, and 7.3% of the subjects with OCS met diagnostic criteria of possible psychotic disorder. The frequent co-occurrence of OCD and psychotic disorders are well documented in epidemiological and clinical studies [4,9,16,17,27,39,41,45,46,55]; and possible pathophysiological overlapping between OCD and psychotic disorders has been suggested [24,56]. Nevertheless, in a study by de Haan and colleagues [12] psychotic disorders were present in only 1.7% of patients with OCD, and De Haan and colleagues [13] suggested that treatment of psychosis induces OCS or OCD in some patients with a primary diagnosis of psychosis.…”
Section: Discussionmentioning
confidence: 99%